Encouraging death communication in a death-avoidant society: analysis of interviews with death café organizers - Kae Ito; Shuji Tsuda; Mayumi Hagiwara; Tsuyoshi Okamura (BMC, 2023)
Abstract Background Post-war Japanese tend to avoid discussion of death, resulting in a lack of death communication within clinical settings. However, with the aging of society, the significance of conversations and decisions related to end-of-life issues has grown. In 2007, the government established guidelines for decision-making in end-of-life care. Nonetheless, death communication remains a challenge for healthcare professionals in clinical settings. In contrast, death cafés have spontaneously emerged within communities as informal gatherings to openly discuss and explore death. Learning from death café organizers may help healthcare professionals encourage death communication in a death-avoidant society. Therefore, a qualitative study was conducted to describe death cafés by examining the underlying motivation and practices through interviews with death café organizers. Methods Individual in-depth interviews were conducted with death café organizers. Two key aspects were explored: 1) the underlying motivations of organizers; and 2) the practices and challenges encountered in running death cafés. The interviews were transcribed verbatim and analyzed using a qualitative descriptive approach. Thematic analysis was used. Results The study identified two themes representing the underlying motivation of death café organizers: individually-oriented and community-oriented. These themes exhibited contrasting orientations and were collectively termed "individual-community orientation". Regarding the practice of death cafés, the focus was on the "attitude towards having attendees with and without grief in the same session." Participants' attitudes towards this aspect fell into two categories with opposing orientations: "purification" and "inclusion." The "purification-inclusion orientation" was more prevalent among organizers who initiated death cafés due to their personal experiences. A matrix was created to categorize death cafés based on their underlying motivations (individual vs. community-oriented) and practices (purification vs. inclusion). This classification resulted in quadrant 1 (community-oriented, inclusive) and quadrant 3 (individually-oriented, purification). Notably, death cafés in quadrant 1 were often held in temples. Conclusions Japanese death cafés can be classified into two categories: individually and purification-oriented and community and inclusive-oriented categories. Healthcare professionals can learn valuable insights from death café organizers, particularly in promoting death communication. Specifically, temple death cafés, with their inclusive practices and orientation towards community, can be particularly beneficial in fostering inclusivity and community engagement.